"denk an Pasolinis ‘verzweifelte Leere von Casarsa’ ": Considerations on the Influence of Spanish Mysticism and of Pasolini’s ‘Friulian’ Poems on Peter Handke’s Noch einmal für Thukydides and Versuch über die Jukebox - Pulimanti, Alessandro (2022)
The present paper aims to highlight the multicultural nature of Peter Handke’s work. Since Handke’s literature seems to also be influenced by the Romance tradition, the present paper will first concentrate on the importance of Pier Paolo Pasolini’s poems in Handke’s works. As remarked by Kitzmüller (2001), the Handke acts as an editor for a German edition of Pasolini’s Poems in Casarsa, which seem to take on a special significance in Handke’s fragments Once Again for Thucydides and in his “Essay on the Jukebox” as well. The paper will finally consider anthropological studies to explore the ethno-folkloric topic in Handke’s literature. In the novel Don Juan the element of the ‘hawthorn’ and the topic of ‘snow’ could be connected to the mythical “Frau Holle”, who refers to the tradition of Grimm’s Fairy Tales and to the ‘Benandanti’ as well. According to Ginzburg’s studies (1989), these mystical female figures belonging to the Friulian folklore are supposed to represent the battle against the Inquisition with the lead of a young fairy celebrated as a goddess. The comparative method and anthropological studies can finally allow us to point out the original role that an apparently ‘small’ Romance language seems to play in Handke’s works.
Keywords: Handke, Peter; Pasolini, Pier Paolo